ASSESSMENT OF A LOW-COST SIDE-SCAN SONAR FOR RIVER ESTUARY UNDERWATER IMAGING - Febriawan, Hendra Kurnia (Laboratory for Marine Survey Technology, 2020)
River and estuary areas commonly exhibit complex and heterogeneous habitats. Thus, revealing the distribution of riverbed morphologies could promote the area management and habitats protection. Since the remote sensing method and manual survey are limited to use, side-scan sonar performs an expectant outcome in underwater habitat imaging. In shallow water and stream areas, low-cost side-scan sonar imaging has become a notable subject of study, yet its use in Indonesia is still limited. This study describes an investigation of the use of a recreational-grade side-scan sonar for stream underwater imaging. A visual inspection and interpretation were implemented using a free-cost sonar software. The result shows some underwater objects and debris could be portrayed perfectly and this indicates that the inexpensive sonar system is appropriate to be used in shallow water and stream areas with a non-rough sea surface. It is suggested that this system could provide a satisfactory product to the users who do not require high accuracy and high resolution of riverbed imagery.Keywords: estuary, river, underwater mapping, acoustic remote sensing, low-cost, side-scan sonar.